Multivariate analysis of factors affecting the immunogenicity of trivalent inactivated influenza vaccine in school-age children - FREEMAN, G. (Epidemiol Infect, 2015)
We examined factors affecting the immunogenicity of trivalent inactivated influenza vaccination (TIV) in children using the antibody titres of children participating in a Hong Kong community-based study. Antibody titres of strains included in the 2009–2010 northern hemisphere TIV [seasonal A(H1N1), seasonal A(H3N2) and B (Victoria lineage)] and those not included in the TIV [2009 pandemic A(H1N1) and B (Yamagata lineage)] were measured by haemagglutination inhibition immediately before and 1 month after vaccination. Multivariate regression models were fitted in a Bayesian framework to characterize the distribution of changes in antibody titres following vaccination. Statistically significant rises in geometric mean antibody titres were observed against all strains, with a wide variety of standard deviations and correlations in rises observed, with the influenza type B antibodies showing more variability than the type A antibodies. The dynamics of antibody titres after vaccination can be used in more complex models of antibody dynamics in populations.